Risk-Based Public Procurement Corruption Prevention Strategy in the Palembang City Government - Muhammad Fadil Hidayat; Yusman Syaukat; Harianto Harianto (International Journal of Economics Development Research (IJEDR), 2023)
Government procurement is the most vulnerable government activity to corruption, especially in the era of decentralization, which grants local governments the authority to manage their domestic affairs independently. The results of the Financial Audit Agency's (BPK) examination of the Palembang City Government in 2022 revealed indications of price manipulation, specifications favoring specific products and contractors, and goods and services produced not complying with the provisions in the contract. This research aims to formulate an anti-corruption strategy for government procurement based on corruption risk. The methods used in this research include descriptive analysis with a literature review, quantitative analysis using Fuzzy Synthetic Evaluation (FSE), and strategy formulation using the Multicriteria Policy (Multipol) method involving government procurement stakeholders. The research findings indicate that the governance of government procurement in Palembang City is still inadequate, with the highest risks being related to implementer integrity, contract execution control, and procurement planning risks. Relevant anti-corruption strategies include the utilization of e-procurement, enhancing human resources and the Procurement Service Unit's (UKPBJ) competence, improving the quality of planning, and strengthening supervision and stakeholder participation.